Estimation of driver alertness to different colors and intensities using brain visual evoked potentials - Bekdash, M. (Institute of Electrical and Electronics Engineers Inc., 2017)
The study investigates the effects of street light colors on driver alertness in aim to improve the traffic safety element. In order to achieve this objective, the human P100 visual evoked potentials (VEPs) responses are stimulated to different colors (red, green, blue, and yellow) with to levels of intensity, and twenty (20) healthy subjects with normal or corrected to normal vision are involved. The P100 responses are recorded using checkerboard stimulus and obtained signals are analyzed in terms of their peaks amplitude and latency (high amplitude with early peak latency indicate a high response). Results show a variation within the human P100 VEPs and most subjects record low responses, when blue color is presented, whilst yellow induces the highest. Moreover, the color intensity level plays a major role in motivating the human alertness as higher responses are recorded, when the intensity is increased. This study shows that a solid relation between chromatic stimulation and human alertness exists. Thus, using the proper color combination to design the road signs may enhance the driver alertness and insure a high level of awareness. © 2016 IEEE.